Preparation method of hindered phenol antioxidant

By using a supported solid base catalyst for transesterification reaction, the antioxidant 1076 was prepared, which solved the problems of equipment corrosion, complex post-treatment and catalyst toxicity in the existing processes, and achieved high yield and low loss catalytic effects and economic benefits.

CN119504423APending Publication Date: 2025-02-25ZHEJIANG DONGJIANG GREEN PETROCHEMICAL TECHNOLOGY INNOVATION CENTER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411407964.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the preparation process of the existing antioxidant 1076, homogeneous catalysts cause serious corrosion of the equipment, complex post-treatment, poor economic performance, and high toxicity of the organotin catalyst, low reaction rate, high metal content of the product, and limited use range.

Method used

An antioxidant 1076 was prepared by using a heterogeneous solid base catalyst, using cellulose and carboxymethyl cellulose as support, combining ammonium polyphosphate and metal oxides as a support, and carrying out a transesterification reaction.

Benefits of technology

The product yield is improved, the catalyst has high reaction selectivity, easy separation from the product, and can still maintain high catalytic activity after recycling, simple process and good economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077199800000011
    Figure BDA0005077199800000011
  • Figure BDA0005077199800000091
    Figure BDA0005077199800000091
  • Figure BDA0005077199800000101
    Figure BDA0005077199800000101
Patent Text Reader

Abstract

The invention relates to the technical field of compound synthesis, and discloses a hindered phenol antioxidant preparation method, which comprises: (1) dispersing cellulose and carboxymethyl cellulose in water, adding a polyimide DMF solution, stirring, adding a PAE wet strength agent, carrying out freeze molding, and carrying out freeze drying; (2) immersing the carrier into an ammonium polyphosphate aqueous solution, taking out, and calcining for the first time; and (3) immersing the carrier into the dispersion liquid of the metal oxide, taking out the carrier, and calcining for the second time to prepare the catalyst, and (4) mixing the beta-(3, 5-di-tert-butyl-4-hydroxyphenyl) methyl propionate, n-octadecanol and a catalyst, and carrying out a reaction so as to obtain the beta-(3, 5-di-tert-butyl-4-hydroxyphenyl) methyl propionate. According to the method, the antioxidant 1076 is catalytically synthesized by adopting the supported solid base catalyst, and the catalyst can be recycled through simple separation and still can show relatively good catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of compound synthesis, in particular to a method for preparing a hindered phenol antioxidant. Background Art

[0002] β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester (antioxidant 1076) is a monophenol lipid with excellent performance. It is one of the representative products among monophenol antioxidants. It is widely used in polystyrene, polyacetal, ABS resin, polyamide polymer and some food packaging materials because of its low toxicity, low melting point (50-55°C), odorless, good compatibility with polymer resins, high extraction resistance, high oxidation resistance, difficult to color, low volatility, no pollution and anti-washing. The structural formula is as follows:

[0003] At present, the preparation of antioxidant 1076 in industry is obtained by transesterification reaction using β-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate and n-octadecanol as raw materials. The selection of catalyst is the core process of the synthesis process of antioxidant 1076. The existing synthesis process catalyst generally uses strong bases (lithium acetate, potassium tert-butoxide, sodium methoxide, sodium hydroxide, etc.) and organotin. The strong base is selected as the catalyst for transesterification because the stronger the alkalinity of the catalyst, the more conducive it is to the forward reaction. However, the traditional strong alkaline catalyst for preparing antioxidant 1076 is basically a homogeneous catalyst. Although the catalytic effect is good, the corrosion to the equipment is more serious, and the post-processing is complicated, and the recyclability and economy are poor. The toxicity of organotin catalysts is high, the reaction rate is low, and the organic metal is difficult to remove, resulting in a high metal content in the product, and the scope of product use is limited.

[0004] For example, the invention patent with application number CN201611031817.0 discloses a method for synthesizing antioxidant 1076, which is prepared by transesterification reaction using β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and n-octadecyl alcohol as raw materials, and the transesterification reaction is carried out in a neutral / weakly alkaline ionic liquid catalytic system. However, the reaction belongs to a homogeneous reaction system, and although the ionic liquid after the reaction can be extracted and separated by adding an external solvent, the preparation of the ionic liquid is cumbersome, and the post-reaction treatment requires the addition of solvent phase separation to separate the catalyst, making the process complicated, and the extraction and liquid separation process will lose part of the product, and the economic efficiency is poor.

[0005] Solid superbase is a strong alkaline solid material that has shown excellent catalytic effects in a variety of catalytic reactions, such as transesterification, olefin isomerization, Michael addition, etc. Solid superbase has high catalytic activity, mild reaction conditions, good heat resistance, high reaction selectivity, easy separation from the product, simple process, can be recycled, and is less corrosive to equipment. Therefore, these advantages of solid superbase can overcome the shortcomings in the synthesis reaction of antioxidant 1076. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a hindered phenol antioxidant, which adopts a heterogeneous solid base catalyst to catalyze the synthesis of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (i.e., antioxidant 1076). The obtained product has a high yield, and the solid base catalyst has a high reaction selectivity, is easy to separate from the product, and can still maintain a high catalytic activity after recycling.

[0007] The purpose of the present invention is achieved through the following technical solutions: The present invention provides a method for preparing a hindered phenol antioxidant, comprising the following steps: (1) Dispersing cellulose and carboxymethyl cellulose in water, adding a DMF solution of polyimide and stirring, then adding a PAE wet strength agent and freeze-molding and freeze-drying; (2) immersing the support in step (1) in an aqueous solution of ammonium polyphosphate, taking it out and performing a first calcination; (3) immersing the support in step (2) in a dispersion of a metal oxide, wherein the metal is one or more of calcium, strontium, barium, yttrium, lanthanum, neodymium, cerium, zirconium and tin, taking out the support and performing a second calcination to obtain a catalyst; (4) β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid methyl ester, n-octadecanol and a catalyst are mixed and reacted to obtain a product.

[0008] The present invention adopts β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and n-octadecanol to carry out ester exchange reaction under the condition of solid base catalyst, and obtains antioxidant 1076. Wherein, the solid base catalyst is a supported catalyst, and the porous hydrogel obtained by crosslinking cellulose and carboxymethyl cellulose with PAE wet strength agent is used as a carrier, and the carrier is immersed in an ammonium polyphosphate aqueous solution for loading. Ammonium polyphosphate will form colloidal particles when added to water, and can achieve good loading effect in the porous hydrogel carrier. After calcination and heating at 200-300° C., ammonium polyphosphate will be thermally decomposed to generate ammonia, water and phosphoric acid, and at the same time promote the dehydration and carbonization of organic matter, which is beneficial to the surface acidity and porous formation of the carrier, and then is beneficial to the dispersed loading of metal oxides. Then, a second calcination is carried out at 500-900° C., which can promote further carbonization of the carrier, increase the specific surface area, and optimize the binding property of the metal oxide and the carrier. In addition, the polyimide and ammonium polyphosphate added to the carrier will cooperate with the metal oxide in the N and P elements after calcination to exert a better catalytic effect. At the same time, polyimide will make the carrier have better thermal stability and mechanical strength during the first calcination, and can maintain high strength and structural integrity even at high temperatures, so that the carrier can have a better loading effect when loading metal oxides, and the resulting catalyst can also maintain a good catalytic effect during recycling.

[0009] Preferably, in step (1), the mass concentration of the cellulose dispersed in water is 0.2-0.4%; the mass concentration of the DMF solution of the polyimide is 15-20%.

[0010] Preferably, in step (1), the amounts of carboxymethyl cellulose, polyimide and PAE wet strength agent are 20-30%, 35-40% and 20-30% of the mass of cellulose, respectively.

[0011] The addition of carboxymethyl cellulose makes the combination compatibility between the cellulose matrix and the polyimide higher, and the stability of the carrier molding is improved through the entanglement and hydrogen bonding between the macromolecular chains, the cross-linking effect of the PAE wet strength agent, and freezing.

[0012] Preferably, in step (1), the freezing molding temperature is -10°C and the time is 12-24 hours.

[0013] Preferably, in step (2), the mass volume ratio of the carrier to the ammonium polyphosphate aqueous solution is 1 g:8-10 mL; and the concentration of the ammonium polyphosphate aqueous solution is 20-30 g / L.

[0014] Preferably, in step (2), the first calcination is performed at 200 to 300° C. for 30 to 100 minutes.

[0015] Preferably, in step (3), the mass volume ratio of the carrier to the dispersion of the metal oxide is 1 g: 8-10 mL.

[0016] Preferably, in step (3), the total concentration of the metal oxides in the metal oxide dispersion is 0.5 to 0.7 mol / L.

[0017] Preferably, in step (3), the second calcination is performed at 600-800° C. for 2-3 hours.

[0018] Preferably, in step (4), the reaction temperature is 120 to 140° C., the reaction time is 2 to 4 hours, and the pressure is -0.2 to -0.1 MPa.

[0019] Preferably, in step (4), the molar ratio of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to n-octadecanol is 1:1 to 1.05.

[0020] Preferably, in step (4), the mass ratio of the catalyst to methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1 to 3:100.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) Antioxidant 1076 is synthesized by using a heterogeneous solid base catalyst, and the catalyst can be recovered and reused by simple separation, thereby improving the shortcomings of the existing preparation technology; (2) The catalyst is a supported catalyst with a high loading rate. The doped elements in the support will work together with the supported metal elements to exert a better catalytic effect, so that the catalyst can still show good catalytic activity after multiple cycles of use; (3) The preparation process of the present invention is simple and has good economic benefits. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0023] The preparation of hindered phenol antioxidant 1076 comprises the following steps: (1) Dispersing cellulose and carboxymethyl cellulose in water, wherein the mass concentration of cellulose in water is 0.2-0.4%, adding a DMF solution of polyimide with a mass concentration of 15-20% and stirring for 1-2 hours, then adding a PAE wet strength agent and stirring for 3-5 hours, wherein the amounts of carboxymethyl cellulose, polyimide and PAE wet strength agent are 20-30%, 35-40% and 20-30% of the mass of cellulose, respectively, and finally freeze-molding at -10°C for 12-24 hours, and then freeze-drying at -20°C for 12-18 hours; (2) immersing the carrier in step (1) in an aqueous solution of ammonium polyphosphate having a concentration of 20-30 g / L for 10-30 min, wherein the mass volume ratio of the carrier to the aqueous solution of ammonium polyphosphate is 1 g:8-10 mL, filtering and freeze-drying, calcining for the first time at 200-300° C. for 30-100 min, with a heating rate of 3-5° C. / min, and cooling after calcination; (3) immersing the support in step (2) in a dispersion of a metal oxide having a total concentration of 0.5 to 0.7 mol / L (the solvent is anhydrous ethanol) for 10 to 30 minutes, wherein the mass volume ratio of the support to the dispersion of the metal oxide is 1 g: 8 to 10 mL, and the metal is one or more of calcium, strontium, barium, yttrium, lanthanum, neodymium, cerium, zirconium and tin; filtering and drying, calcining for a second time at 600 to 800° C. for 2 to 3 hours, with a heating rate of 6 to 10° C. / min; cooling after calcination to obtain a catalyst; (4) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol in a molar ratio of 1:1 to 1.05, a catalyst accounting for 1 to 3% by mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is added and mixed, and then reacted at a temperature of 120 to 140° C. and a pressure of -0.2 to -0.1 MPa for 2 to 4 hours to obtain antioxidant 1076.

[0024] In a specific embodiment of the present invention, cellulose is cellulose powder; carboxymethyl cellulose is carboxymethyl cellulose powder, 300-800 mPa·s; polyimide is soluble polyimide powder, with a glass transition temperature (Tg) of 320-330°C, a temperature of 5% thermal weight loss of about 525°C, and an intrinsic viscosity of 0.5-0.7 dl / g; PAE wet strength agent is the full name of polyamide polyepichlorohydrin resin, which is a water-soluble, cationic, thermosetting resin; ammonium polyphosphate is water-soluble ammonium polyphosphate, and the average degree of polymerization is 35-55.

[0025] Example 1 (1) Cellulose and carboxymethyl cellulose were dispersed in water, the mass concentration of cellulose in water was 0.3%, and then a DMF solution of polyimide with a mass concentration of 18% was added and stirred for 1.5 hours. Then, a PAE wet strength agent was added and stirred for 4 hours, wherein the amounts of carboxymethyl cellulose, polyimide and PAE wet strength agent were 23%, 40% and 25% of the mass of cellulose, respectively. Finally, the mixture was freeze-molded at -10°C for 24 hours, and then freeze-dried at -20°C for 16 hours.

[0026] (2) Immerse the carrier in step (1) in an aqueous solution of ammonium polyphosphate with a concentration of 20 g / L for 30 min, wherein the mass volume ratio of the carrier to the aqueous solution of ammonium polyphosphate is 1 g:8 mL. After filtering and freeze-drying at -20°C for 5 h, the carrier is calcined for the first time at 250°C for 50 min at a heating rate of 4°C / min. After calcination, the carrier is cooled.

[0027] (3) Immerse the carrier in step (2) in a dispersion of metal oxides (calcium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) with a total concentration of 0.65 mol / L for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 800°C for 2 h, with a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0028] (4) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol at a molar ratio of 1:1.05, a catalyst accounting for 2% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and the mixture was replaced with nitrogen three times to replace the air in the reactor, and then vacuum was evacuated to a pressure of -0.1 MPa. Then, the temperature was raised to 140° C. and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered while hot, and the resulting liquid was recrystallized to obtain antioxidant 1076.

[0029] Example 2 (1) Cellulose and carboxymethyl cellulose are dispersed in water, wherein the mass concentration of cellulose in water is 0.2%. A DMF solution of polyimide with a mass concentration of 20% is then added and stirred for 2 h. A PAE wet strength agent is then added and stirred for 5 h, wherein the amounts of carboxymethyl cellulose, polyimide and PAE wet strength agent are 30%, 35% and 30% of the mass of cellulose, respectively. Finally, the mixture is freeze-molded at -10°C for 20 h, and then freeze-dried at -20°C for 18 h.

[0030] (2) Immerse the carrier in step (1) in an aqueous solution of ammonium polyphosphate with a concentration of 25 g / L for 20 min, wherein the mass volume ratio of the carrier to the aqueous solution of ammonium polyphosphate is 1 g:10 mL. After filtering and freeze-drying at -20°C for 5 h, the carrier is calcined for the first time at 250°C for 50 min at a heating rate of 4°C / min. After calcination, the carrier is cooled.

[0031] (3) Immerse the carrier in step (2) in a dispersion of metal oxides (calcium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) with a total concentration of 0.55 mol / L for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 800°C for 2 h, with a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0032] (4) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol at a molar ratio of 1:1.05, a catalyst accounting for 2% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and the mixture was replaced with nitrogen three times to replace the air in the reactor, and then vacuum was evacuated to a pressure of -0.1 MPa. Then, the temperature was raised to 140° C. and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered while hot, and the resulting liquid was recrystallized to obtain antioxidant 1076.

[0033] Example 3 (1) Cellulose and carboxymethyl cellulose are dispersed in water, wherein the mass concentration of cellulose in water is 0.4%. A DMF solution of polyimide with a mass concentration of 15% is then added and stirred for 1 hour. Then, a PAE wet strength agent is added and stirred for 3 hours, wherein the amounts of carboxymethyl cellulose, polyimide and PAE wet strength agent are 20%, 40% and 25% of the mass of cellulose, respectively. Finally, the mixture is freeze-formed at -10°C for 24 hours and then freeze-dried at -20°C for 16 hours.

[0034] (2) Immerse the carrier in step (1) in an aqueous solution of ammonium polyphosphate with a concentration of 20 g / L for 20 min, wherein the mass volume ratio of the carrier to the aqueous solution of ammonium polyphosphate is 1 g:8 mL. After filtering and freeze-drying at -20°C for 5 h, the carrier is calcined at 300°C for the first time for 40 min at a heating rate of 3°C / min. After calcination, the carrier is cooled.

[0035] (3) Immerse the carrier in step (2) in a dispersion of metal oxides with a total concentration of 0.7 mol / L (calcium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for a second time at 800°C for 3 h at a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0036] (4) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol at a molar ratio of 1:1.05, a catalyst accounting for 2% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and the mixture was replaced with nitrogen three times to replace the air in the reactor, and then vacuum was evacuated to a pressure of -0.1 MPa. Then, the temperature was raised to 140° C. and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered while hot, and the resulting liquid was recrystallized to obtain antioxidant 1076.

[0037] Example 4 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of strontium oxide.

[0038] (3) Immerse the carrier in step (2) in a dispersion of metal oxide with a total concentration of 0.65 mol / L (strontium oxide with an average particle size of 5 μm, and the solvent is anhydrous ethanol) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxide is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 800°C for 2 h, with a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0039] Example 5 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of barium oxide.

[0040] (3) Immerse the carrier in step (2) in a dispersion of a metal oxide having a total concentration of 0.65 mol / L (barium oxide having an average particle size of 100 nm, and anhydrous ethanol as the solvent) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxide is 1 g:10 mL. After filtering and drying at 60° C., calcinate the carrier for a second time at 800° C. for 2 h, with a heating rate of 8° C. / min. After calcination, cool the carrier to obtain a catalyst.

[0041] Example 6 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of yttrium oxide.

[0042] (3) Immerse the carrier in step (2) in a dispersion of a metal oxide with a total concentration of 0.65 mol / L (yttrium oxide with an average particle size of 100 nm, and the solvent is anhydrous ethanol) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxide is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for a second time at 600°C for 3 h at a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0043] Example 7 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of lanthanum oxide.

[0044] (3) Immerse the carrier in step (2) in a dispersion of metal oxides with a total concentration of 0.65 mol / L (lanthanum oxide with an average particle size of 1 μm, and anhydrous ethanol as the solvent) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 600°C for 3 h at a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0045] Example 8 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of neodymium oxide.

[0046] (3) Immerse the carrier in step (2) in a dispersion of a metal oxide having a total concentration of 0.65 mol / L (neodymium oxide having an average particle size of 1 μm, and the solvent is anhydrous ethanol) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxide is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 600°C for 3 h at a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0047] Example 9 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of cerium oxide.

[0048] (3) Immerse the carrier in step (2) in a dispersion of a metal oxide with a total concentration of 0.65 mol / L (cerium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxide is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for a second time at 600°C for 3 h at a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0049] Example 10 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of zirconium oxide.

[0050] (3) Immerse the carrier in step (2) in a dispersion of metal oxides (zirconium oxide with an average particle size of 1 μm, and anhydrous ethanol as the solvent) with a total concentration of 0.65 mol / L for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 600°C for 3 h at a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0051] Embodiment 11 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of tin oxide.

[0052] (3) Immerse the carrier in step (2) in a dispersion of metal oxides (tin oxide with an average particle size of 1 μm, and anhydrous ethanol as the solvent) with a total concentration of 0.65 mol / L for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 600°C for 3 h at a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0053] Comparative Example 1 The difference from Example 1 is that no carrier is added to the catalyst.

[0054] (1) Weigh 200 g of calcium carbonate, grind it into powder, heat it to 900° C. and keep it for 1.5 h at a heating rate of 8° C. / min. After calcination, cool it to obtain a catalyst.

[0055] (2) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol at a molar ratio of 1:1.05, a catalyst accounting for 2% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and the mixture was replaced with nitrogen three times to replace the air in the reactor, and then vacuum was evacuated to a pressure of -0.1 MPa. Then, the temperature was raised to 140° C. and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered while hot, and the resulting liquid was recrystallized to obtain antioxidant 1076.

[0056] Comparative Example 2 The difference from Example 1 is that in step (3), the dispersion of the metal oxide is a dispersion of magnesium oxide.

[0057] (3) Immerse the carrier in step (2) in a dispersion of metal oxides (magnesium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) with a total concentration of 0.65 mol / L for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 800°C for 2 h, with a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0058] Comparative Example 3 The difference from Example 1 is that no polyimide is added to the catalyst.

[0059] (1) Cellulose and carboxymethyl cellulose were dispersed in water, the mass concentration of cellulose in water was 0.3%, and then PAE wet strength agent was added and stirred for 4 hours, wherein the amount of carboxymethyl cellulose and PAE wet strength agent was 23% and 25% of the mass of cellulose, respectively. Finally, the mixture was freeze-formed at -10°C for 24 hours and then freeze-dried at -20°C for 16 hours.

[0060] (2) Immerse the carrier in step (1) in an aqueous solution of ammonium polyphosphate with a concentration of 20 g / L for 30 min, wherein the mass volume ratio of the carrier to the aqueous solution of ammonium polyphosphate is 1 g:8 mL. After filtering and freeze-drying at -20°C for 5 h, the carrier is calcined for the first time at 250°C for 50 min at a heating rate of 4°C / min. After calcination, the carrier is cooled.

[0061] (3) Immerse the carrier in step (2) in a dispersion of metal oxides (calcium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) with a total concentration of 0.65 mol / L for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 800°C for 2 h, with a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0062] (4) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol at a molar ratio of 1:1.05, a catalyst accounting for 2% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and the mixture was replaced with nitrogen three times to replace the air in the reactor, and then vacuum was evacuated to a pressure of -0.1 MPa. Then, the temperature was raised to 140° C. and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered while hot, and the resulting liquid was recrystallized to obtain antioxidant 1076.

[0063] Comparative Example 4 The difference from Example 1 is that ammonium polyphosphate is not added to the catalyst.

[0064] (1) Cellulose and carboxymethyl cellulose were dispersed in water, the mass concentration of cellulose in water was 0.3%, and then a DMF solution of polyimide with a mass concentration of 18% was added and stirred for 1.5 hours. Then, a PAE wet strength agent was added and stirred for 4 hours, wherein the amounts of carboxymethyl cellulose, polyimide and PAE wet strength agent were 23%, 40% and 25% of the mass of cellulose, respectively. Finally, the mixture was freeze-molded at -10°C for 24 hours, and then freeze-dried at -20°C for 16 hours.

[0065] (2) The carrier in step (1) was first calcined at 250° C. for 50 min at a heating rate of 4° C. / min, and then cooled after calcination.

[0066] (3) Immerse the carrier in step (2) in a dispersion of metal oxides (calcium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) with a total concentration of 0.65 mol / L for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate the carrier for the second time at 800°C for 2 h, with a heating rate of 8°C / min. After calcination, cool the carrier to obtain a catalyst.

[0067] (4) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol at a molar ratio of 1:1.05, a catalyst accounting for 2% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and the mixture was replaced with nitrogen three times to replace the air in the reactor, and then vacuum was evacuated to a pressure of -0.1 MPa. Then, the temperature was raised to 140° C. and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered while hot, and the resulting liquid was recrystallized to obtain antioxidant 1076.

[0068] Comparative Example 5 The difference from Example 1 is that the catalyst carrier is not subjected to calcination treatment at 200-300°C.

[0069] (1) Cellulose and carboxymethyl cellulose were dispersed in water, the mass concentration of cellulose in water was 0.3%, and then a DMF solution of polyimide with a mass concentration of 18% was added and stirred for 1.5 hours. Then, a PAE wet strength agent was added and stirred for 4 hours, wherein the amounts of carboxymethyl cellulose, polyimide and PAE wet strength agent were 23%, 40% and 25% of the mass of cellulose, respectively. Finally, the mixture was freeze-molded at -10°C for 24 hours, and then freeze-dried at -20°C for 16 hours.

[0070] (2) The carrier in step (1) was immersed in an aqueous solution of ammonium polyphosphate with a concentration of 20 g / L for 30 min, the mass volume ratio of the carrier to the aqueous solution of ammonium polyphosphate was 1 g:8 mL, and the mixture was filtered and freeze-dried at -20°C for 5 h.

[0071] (3) Immerse the carrier in step (2) in a dispersion of metal oxides with a total concentration of 0.65 mol / L (calcium oxide with an average particle size of 100 nm, and anhydrous ethanol as the solvent) for 30 min, wherein the mass volume ratio of the carrier to the dispersion of the metal oxides is 1 g:10 mL. After filtering and drying at 60°C, calcinate at 800°C for 2 h at a heating rate of 8°C / min. After calcination, cool the mixture to obtain a catalyst.

[0072] (4) After mixing methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecanol at a molar ratio of 1:1.05, a catalyst accounting for 2% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and the mixture was replaced with nitrogen three times to replace the air in the reactor, and then vacuum was evacuated to a pressure of -0.1 MPa. Then, the temperature was raised to 140° C. and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered while hot, and the resulting liquid was recrystallized to obtain antioxidant 1076.

[0073] The yield of the target product β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate was shown by high performance liquid chromatography (HPLC), and the product color was pure white. The solid catalyst was washed with ethanol and then vacuum dried before being used in the next catalytic cycle, and then used in the preparation of antioxidant 1076 according to the above method, and the yield of the target product was measured again.

[0074] Table 1 As shown in Table 1, the initial product yield obtained in Examples 1-11 and the product yield after 5 cycles are both high, the recovery loss rate of the catalyst is low, and a high catalytic activity can still be maintained. In Comparative Example 1, since no carrier loading is performed, the loss rate of the catalyst during the recycling process is high, and a high catalytic activity cannot be maintained, and the product yield is significantly reduced. Comparative Example 2 shows that the type of metal oxide will also affect the catalytic activity of the catalyst. Not all alkaline metals can exert a good catalytic synergistic effect with the carrier, and the catalytic effect will be different for different substrates and environmental factors such as reaction conditions. Moreover, the preparation of the carrier in the catalyst will also have a greater impact on the catalytic effect. Comparative Examples 3-5 show that the addition of polyimide in the catalyst will affect the structural stability, and the addition of ammonium polyphosphate and the corresponding calcination treatment at 200-300°C will affect the loading effect, which will in turn affect the product yield.

[0075] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a hindered phenol antioxidant, characterized in that: The steps include: (1) Disperse cellulose and carboxymethyl cellulose in water, add DMF solution of polyimide and stir, then add PAE wet strength agent and freeze-form and freeze-dry; (2) immersing the support in step (1) in an aqueous solution of ammonium polyphosphate, taking it out and performing a first calcination; (3) immersing the support in step (2) in a dispersion of a metal oxide, wherein the metal is one or more of calcium, strontium, barium, yttrium, lanthanum, neodymium, cerium, zirconium and tin, taking out the support and performing a second calcination to obtain a catalyst; (4) β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid methyl ester, n-octadecanol and a catalyst are mixed and reacted to obtain a product.

2. The method for preparing the hindered phenol antioxidant according to claim 1, characterized in that: In step (1), the mass concentration of the cellulose dispersed in water is 0.2-0.4%; the mass concentration of the DMF solution of the polyimide is 15-20%.

3. The method for preparing the hindered phenol antioxidant according to claim 1 or 2, characterized in that: In step (1), the dosage of the carboxymethyl cellulose, polyimide and PAE wet strength agent is 20-30%, 35-40% and 20-30% of the cellulose mass respectively; the freezing molding temperature is -10°C and the time is 24-36h.

4. The method for preparing the hindered phenol antioxidant according to claim 1, characterized in that: In step (2), the mass volume ratio of the carrier to the ammonium polyphosphate aqueous solution is 1 g:8-10 mL; and the concentration of the ammonium polyphosphate aqueous solution is 20-30 g / L.

5. The method for preparing the hindered phenol antioxidant according to claim 1 or 4, characterized in that: In step (2), the first calcination is performed at 200-300° C. for 30-100 min.

6. The method for preparing the hindered phenol antioxidant according to claim 1, characterized in that: In step (3), the mass volume ratio of the carrier to the metal oxide dispersion is 1 g: 8-10 mL; and the total concentration of the metal oxide in the metal oxide dispersion is 0.5-0.7 mol / L.

7. The method for preparing the hindered phenol antioxidant according to claim 1 or 6, characterized in that: In step (3), the second calcination is carried out at 600-800°C for 2-3 hours.

8. The method for preparing the hindered phenol antioxidant according to claim 1, characterized in that: In step (4), the reaction temperature is 120-140°C, the reaction time is 2-4 h, and the pressure is -0.2-0.1 MPa.

9. The method for preparing the hindered phenol antioxidant according to claim 1, characterized in that: In step (4), the molar ratio of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to n-octadecanol is 1:1 to 1.

05.

10. The method for preparing the hindered phenol antioxidant according to claim 1, 8 or 9, characterized in that: In step (4), the mass ratio of the catalyst to methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1-3:100.

Citation Information

Patent Citations

  • Method for synthesizing antioxygen 1076

    CN106699551A